Didactic materials application to develop speaking skills in the teaching-learning process of English as a foreign language. - Campoverde Tandazo, Jinsop Javier (Machala : Universidad Técnica de Machala, 2015)
It is crucial to be aware of the significance of education for young people, especially in the English language teaching-learning process. The main objective of this research was DIDACTIC MATERIALS APPLICATION TO DEVELOP SPEAKING SKILLS IN THE TEACHING-LEARNING PROCESS OF ENGLISH AS A FOREIGN LANGUAGE.English language acquisition has an increasing importance for the academic formation of the youth in our country. We must look for appropriate means to draw young people's interest in their pursuit of English language acquisition. In consequence, this investigation considers that teaching materials are one of the best means to achieve this goal.
Es crucial ser consciente de la importancia de la educación para los jóvenes , especialmente en el proceso de enseñanza- aprendizaje de idiomas Inglés . El principal objetivo de esta investigación fue DIDÁCTICA MATERIALES aplicaciones desarrollar habilidades para hablar EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE DE INGLÉS COMO adquisición del lenguaje LANGUAGE.English extranjero tiene una importancia creciente para la formación académica de los jóvenes en nuestro país . Hay que buscar los medios apropiados para atraer el interés de los jóvenes en su búsqueda de la adquisición del lenguaje Inglés . En consecuencia , esta investigación considera que los materiales de enseñanza son uno de los mejores medios para lograr este objetivo .
Keywords: DIDATIC; DEVELOP; SPEAKING; FOREIGN